Kata Maaf, Apakah Berarti Damai? Relasi Pasangan Suami-Istri di Pusaran Kekerasan dalam Rumah Tangga - Muhammad Zulfa Alfaruqy; Endang Sri Indrawati (Universitas Muhammadiyah Jember, 2022)
Family is a communal group that has been identified by warmth and affection. Along with the times, unfortunately, many families are getting in phenomena of domestic violence. This study aimed to understand the causes and the dynamics of the marital relationship which get in the vortex of domestic violence. Data retrieval was using interviews, observation, and discussion among three wives whoever got domestic violence. The results of this study show that domestic violence occurs because there is unclear mind and psychological inconveniences may lead to a husband's jealousy until venting the aggressive one toward his wife. The superiority of the husband encourages him to hurt his wife who is more inferior so that the violence occurs. Many kinds of violence that may happen are physical violence, psychological violence, social violence, and household abandonment. A husband’s apology bought his relationship with his wife is getting better. But without peacebuilding, domestic violence is a cycle of repetitive behavior so the husband repeat it again and again The increase of violence’s intensity will be bought to relationship fading. The autonomy of children and the support of the wife’s big family will lead her to decide a divorce.